[INVITED] Silicon nitride photonic integration for visible light applications. (15th April 2019) - Porcel, Marco A.G.; Hinojosa, Alberto; Jans, Hilde; Stassen, Andim; Goyvaerts, Jeroen; Geuzebroek, Douwe; Geiselmann, Michael; Dominguez, Carlos; Artundo, Iñigo
Highlights: SiN PICs are an promising platform to miniaturize optical biosensing systems. Four foundries are offering open-access generic manufacturing. Different methods for sensing where SiN PICs are used are presented. PIX4life is presented as current driver of development of SiN PICs in the visible. Systems on several applications mentioned: OCT, cytometry, sensors, light sources. Abstract: In this article, we provide a review of fabrication platforms and state of the art developments in the area of silicon nitride photonic integrated circuits (PICs) for the visible wavelength range, mostly employed in bio-medical and chemical sensing applications. Additionally, we introduce PIX4life, the European pilot line for silicon nitride PICs for visible applications. PIX4life provides a unified framework for the development of such PICs, including design and software, fabrication, characterization and packaging.